The Effect of the Medical University Studying on the Eating Habits and the Health of Slovak Students (Global Journal of Medical Research, 2023)
Background University studying is demanding on the mental as well as the physical side of the organism However studying medicine is even more challenging the study is six years long and it is tough to remember more information The study changed the social life of students and the students didn t have enough time to relax The examinations of students are full of stress Stress harms health especially in the gastrointestinal tract autonomic nerve system Aims The first study evaluated the relationship between medical university studying university stress-academic stress and eating habits and their effect on student s health We analysed the eating changing during the academic year Methods We made the questionnaire and distributed it to medical students at the Faculty of Medicine in Bratislava Slovakia A total of 587 students from the 1st to 6th year completed selfreport measures of BMI academic stress eating habits and the occurrence or development of digestive problems during the study
Keywords: academic stress; eating habit; gastrointestinal disorders; students